Demystifying Palmar Midcarpal Instability - Jing, Shan Shan; Smith, Gemma; Deshmukh, Subodh (Journal of Wrist Surgery, 2020)
Palmar midcarpal instability is an uncommon condition diagnosed clinically with a painful pathognomonic clunk on terminal ulnar deviation of the wrist. Various causes have been described, but congenital laxity of the carpal ligaments is thought to be a key contributor. Treatment commences with conservative measures. This includes proprioceptive training based on more recent concepts on the sensorimotor function of the wrist. When these measures plateau, surgery is considered. The lack of high-level evidence and consensus on its cause continue to hamper our understanding and knowledge of this condition. The purpose of this review is to examine the current evidence to conceptualize this mysterious, yet infrequent phenomenon, and to provide an algorithm on its management.
Keywords: midcarpal; instability; chronic; hypermobility; arthrodesis; proprioception